Some Problems Of Transitivity In Swahili. - Whiteley, W. H. (Taylor & Francis Ltd., 2004)
During the past two years work has been started on the preparation of a new Swahili dictionary, and while the work is still at an early stage of development it is clear that two particularly difficult problems concern the extent to which lexical material can be systematized, and the manner in which this can best achieved.